Developing and Conducting a Dissertation Study Through the Community-Based Participatory Research Approach. (June 2016) - Nadimpalli, Sarah B.; Van Devanter, Nancy; Kavathe, Rucha; Islam, Nadia
The community-based participatory research (CBPR) approach can be an innovative and effective way to address health disparities. Doctoral students in the health sciences can benefit through structured CBPR training experiences in learning how to engage with communities, build community capacity, share resources, and implement CBPR studies. The objectives of this case study are to demonstrate ways in which one doctoral student aligned with academic mentors and a funded CBPR project to develop and implement a CBPR-focused doctoral dissertation study. The student partook in formal and informal CBPR learning experiences, built community and academic relationships, developed a research plan in collaboration with members of the community/academic partners, identified an appropriate setting and methods for recruitment/data collection, and increased the capacity and resources for all partners (the first author, community, and academic). In conclusion, CBPR-focused doctoral experiences are novel, pedagogical, and professional approaches that can lead to successful and effective community-based health research.